Advances in multi-physics and multi-scale couplings in geo-environmental mechanics - Nicot, Francois; Millet, Olivier (Civil engineering and geomechanics., 2018)
Advances in Multi-Physics and Multi-Scale Couplings in Geo-Environmental Mechanics reunites some of the most recent work from the French research group MeGe GDR (National Research Group on Multiscale and Multiphysics Couplings in Geo-Environmental Mechanics) on the theme of multi-scale and multi-physics modeling of geomaterials, with a special focus on micromechanical aspects. Its offers readers a glimpse into the current state of scientific knowledge in the field, together with the most up-to-date tools and methods of analysis available. Each chapter represents a study with a different viewpoint, alternating between phenomenological/micro-mechanically enriched and purely micromechanical approaches. Throughout the book, contributing authors will highlight advances in geomaterials modeling, while also pointing out practical implications for engineers. Topics discussed include multi-scale modeling of cohesive-less geomaterials, including multi-physical processes, but also the effects of particle breakage, large deformations on the response of the material at the specimen scale and concrete materials, together with clays as cohesive geomaterials. The book concludes by looking at some engineering problems involving larger scales.